Modeling Participant Toward Self-Care Deficit on Schizophrenic Clients - Ah Yusuf; Hanik Endang Nihayati; Krisna Eka Kurniawan (Jurnal Ners, 2017)
Introduction: Scizophrenia is a disease which affect of brain, causing impaired perception, thought, emotion, movement, and behavior, such as self care deficit. Self-care deficit is an impaired ability to bathing, dressing, eating and toileting. Modeling participant is a technique required to address the problem of self-care deficit where clients are taught and trained to meet the needs of self-care. The purpose of this study was to analyze the influence of participants modeling on self-care ability in schizophrenic clients with self-care deficit.Method: This study used quasi experimental design. Sampling was carried out with total sampling to all affordable population comprising 20 respondents in Dr Radjiman Wediodiningrat Mental Hospital, Lawang. This study analyzed by Wilcoxon Signed Rank Test and Mann-Whitney Test with significance level of p < 0.05.Result: The results showed the influence of participants modeling on self-care ability in schizophrenic clients with self-care deficit. Wilcoxon Signed Rank Test in treatment group showed p = 0.005 and control group showed p = 0,206. Mann-Whitney Test showed p = 0.030. Modeling participant improved self-care ability in schizophrenic clients with self-care deficit.Analysis: Modeling participant will improve cognitive, self-confidence and motivation of schizophrenic clients so that their ability to bathing, dressing, eating and toileting will increase.Discussion: Modeling participant can be applied as a technique to improve self-care ability in schizophrenic clients with self-care deficit. For further research can be explored further implementation of the modeling of participants in the group activity theraphy.